2020
DOI: 10.1103/physrevb.101.125105
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid functional calculations of electronic structure and carrier densities in rare-earth monopnictides

Abstract: The structural parameters and electronic structure of rare-earth pnictides are calculated using density functional theory (DFT) with the Heyd, Scuseria, and Ernzerhof (HSE06) screened hybrid functional. We focus on RE-V compounds, with RE=La, Gd, Er, and Lu, and V=As, Sb, and Bi, and analyze the effects of spin-orbit coupling and treating the RE 4f electrons as valence electrons in the projector augmented wave approach. The results of HSE06 calculations are compared with DFT within the generalized gradient app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 70 publications
6
20
0
Order By: Relevance
“…However, GdBi still exhibits the twofold and fourfold symmetric magnetoresistance, as those present in LaSb and LaBi, further verifying the significance of anisotropic electron pockets for the angular magnetoresistance. Referring to ErBi, Khalid et al find that in the ferromagnetic phase its electronic band structure is nearly the same as that of LaBi [60], indicating that the anisotropic electron pockets can be extracted around the E F . Actually, our calculations (see the Supplemental Material [37]) on the ferromagnetic state of ErBi confirm the presence of elongated ellipsoidal electron pockets centered at the X point in the Brillouin zone.…”
Section: Is Substituted By Lubimentioning
confidence: 99%
See 1 more Smart Citation
“…However, GdBi still exhibits the twofold and fourfold symmetric magnetoresistance, as those present in LaSb and LaBi, further verifying the significance of anisotropic electron pockets for the angular magnetoresistance. Referring to ErBi, Khalid et al find that in the ferromagnetic phase its electronic band structure is nearly the same as that of LaBi [60], indicating that the anisotropic electron pockets can be extracted around the E F . Actually, our calculations (see the Supplemental Material [37]) on the ferromagnetic state of ErBi confirm the presence of elongated ellipsoidal electron pockets centered at the X point in the Brillouin zone.…”
Section: Is Substituted By Lubimentioning
confidence: 99%
“…However, GdBi still exhibits the twofold and fourfold symmetric magnetoresistance, as those present in LaSb and LaBi, further verifying the significance of anisotropic electron pockets for the angular magnetoresistance. Referring to ErBi, Khalid et al find that in the ferromagnetic phase its electronic band structure is nearly the same as that of LaBi [59], indicating that the anisotropic electron pockets can be extracted around the EF.…”
Section: (D)mentioning
confidence: 99%
“…For the exchange and correlation, we used the generalized GGA of Perdew-Burke-Ernzerhof ( 45 ). Test calculations based on the screened hybrid functional HSE06 ( 46 , 47 ) were used to overcome the problem of DFT-GGA in overestimating the overlap of the electron and hole pockets in LuSb ( 12 , 48 ) and underestimating the bandgap of GaSb. The effects of spin-orbit coupling are included in all band structure calculations.…”
Section: Methodsmentioning
confidence: 99%
“…However, Charifi et al found that LaN, LaP, and LaAs are semiconductors using both LDA and the generalized gradient approximation (GGA) calculations [37]; Shoaib et al [38] also reached a similar conclusion by using the Wu and Cohen GGA functional [39]. Moreover, Yan et al [40] and Khalid et al [41] reported non-zero energy gaps in LaP and LaAs, by using a more sophisticated Heyde-Scuseriae-Ernserh hybrid functional (HSE06). Since the band structure and energy gap play crucial roles in determining transport and thermoelectric properties, it is important to ensure accurate description and computation of the electronic structures.…”
mentioning
confidence: 99%